2013
DOI: 10.2528/pierc13072904
|View full text |Cite
|
Sign up to set email alerts
|

Complex Rectangular Filter Design Using Hybrid Finite Element Method and Modified Multimodal Variational Formulation

Abstract: Abstract-We hybridize vector Finite Element Method (FEM) and a Modified Multimodal Variational Formulation (MMVF) to the accurate and fast design of complex isotropic rectangular filters. The MMVF is applied to the full-wave description in the rectangular waveguides while the FEM characterizes waves in the arbitrarily shaped discontinuities. The proposed hybrid method is applied to the full-wave analysis of circuits with great practical interest (i.e., cross-shaped iris and multimode filters), thus improving C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…We found that both numerical CAD tools provided similar accuracies for all studied discontinuities which show the versatility of the proposed hybrid method. However, to converge, as presented in our earlier publications for complex rectangular waveguide discontinuities [9][10][11], we find that HFSS takes about 5 hours while our method takes a few minutes which represents an overall reduction in CPU time more than 99% in all studied structures.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…We found that both numerical CAD tools provided similar accuracies for all studied discontinuities which show the versatility of the proposed hybrid method. However, to converge, as presented in our earlier publications for complex rectangular waveguide discontinuities [9][10][11], we find that HFSS takes about 5 hours while our method takes a few minutes which represents an overall reduction in CPU time more than 99% in all studied structures.…”
Section: Resultsmentioning
confidence: 87%
“…Nevertheless, these techniques require important CPU time and memory storage. To alleviate these weaknesses, several hybrid modal and space meshing methods have been proposed [5][6][7][8][9][10][11]. In [9][10][11], we presented hybrid FEM-MVM tools to the studying of complex discontinuities in unfilled and filled rectangular waveguides.…”
Section: Introductionmentioning
confidence: 99%